Virtual induction and treatment of arrhythmias (VITA): a fast automated computational tool to induce scar-related tachycardia and identify ablation targets. (19th May 2022) - Campos, F; Neic, AN; Mendonca Costa, CMC; Whitaker, JW; O'neill, MON; Razavi, RR; Rinaldi, CA; Scherr, DS; Niederer, SAN; Plank, GP; Bishop, MJB
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): British Heart Foundation, Wellcome Trust Background: Catheter ablation therapy of post-infarction ventricular tachycardia (VT) is often a lengthy procedure, with a high risk profile, and VT recurrence remains common. While computational modeling may aid pre-procedure planning and target identification, state-of-the-art reaction diffusion (R-D) simulations require access to high performance computing facilities, making them incompatible with clinical workflows. Purpose: To present the Virtual Induction and Treatment of Arrhythmias (VITA), a novel, fast and fully automated computational tool to induce VT and identify subsequent ablation targets. Methods: VITA employs multisite pacing to automatically find split activation wavefronts associated with the presence of channel isthmuses of viable myocytes within the inexcitable scar. The algorithm probes for all possible associated reentrant pathways and refines these to obtain a set of unique circuits sustaining potential clinical VTs. VT sustenance is assessed by comparing the electrical wavelength with the anatomical circuit path length. Corresponding exit sites of susceptible circuits are automatically identified, and a minimal lesion set constructed for ablation targeting. VITA also allows for rapid simulation of ECGs for clinical comparison. A summary of the VITA is shown in the Figure. VITA was tested on a virtual cohort of 7 post-infarcted porcine hearts and results compared to R-D simulations. Results: Using only a desktop computer, VITA successfully identified all possible scar-related VT circuits and optimal ablation targets in just 48mins (per model), compared to 68.5hrs using a high-performance computer required by the R-D approach. Furthermore, VITA consistently identified more VTs associated with intra-scar circuits than R-D (Figure C). Conclusion: VITA provides the first near real-time computational tool to aid treatment of post-infarction VTs.